Liar Sentence Mirroring Our Reasoning as Hegel’s Quasi-Speculative Sentence - Lee, Jae Jeong (Problemos, 2025)
This paper explores parallels between the Liar and various aspects of philosophical reasoning. It begins by analyzing the liar sentence, “This sentence is false”, by highlighting its self-referential nature and alternating truth values. The paper then draws connections between the Liar and Hegel’s speculative sentence, proposing it as a ‘quasi-speculative sentence’ that mirrors dialectical reasoning. Subsequent sections examine the logocentric predicament, Zeno’s paradox, the realism vs. anti-realism debate, and determinism, illustrating how they embody similar self-negating structures. The analysis sheds light on the underlying structure of our philosophical reasoning.